The phonetic significance of the drawing of letters in the Holy 'Qur’an “Qaloon’s narration as an example' (Journal of Human Sciences, 2024)
This research is concerned with studying the relationship between the letters in the Holy Qur’an and their written symbols in the narration of Qaloon of Nafeh Al-Madani. That is, do the drawn letters represent their standard symbols, or are there deviations from those symbols, so they are represented by more than one symbol when they are replaced by another sound due to a relationship between the two sounds in what is known as substitution or reversal, or similarity, or a historical relationship? What is the significance of drawing a letter with a symbol other than its usual symbol? Rather, what is the phonetic significance of a letter that is drawn with two different symbols in one word or two adjacent words?It should be noted that this research studies what is an actual reality applied in Qaloun’s novel, according to the sources mentioned in this research. By tracing these relationships, it turns out that the double drawing of the letter occurs for phonetic reasons, which the research confirmed through its study of what is known as the feminized ta’ and the bound ha’, and in the drawing of tanween in  an accusative case as  Alpha (ألفاً). The research studied the significance of drawing letters with symbols other than those known to be the standard drawing for them, when they change due to their juxtaposition with what is close to them, and this includes drawing a Ta  ( تاء افتعل )  as dal (دال) if it is preceded by a za (زاي), a dhal ( ذال), or a dal (دال  ) when it is Saakin, so the origin of dal (دال) in all of this is a Ta (تاء). Among them is the drawing of a Ta ( تاء افتعل )  as Taa (طاء), if it is preceded by a sād (صاد), or a dhā (ظاء), or a ḍād (ضاد), or a tā’ (طاء ) and be Saakin, but it is drawn with the new symbol for the pronounced word due to the phonetic laws, where the letter begins with one symbol and goes on to another. The research also dealt with the letter that was drawn with a symbol, but what is pronounced is a different sound. This occurs in the drawing of the Alif as yaa with its origin yaa, such as: فتىا , استسقىـاـه, and رأىا ; and the drawing of the Alif as Waw with its origin  waw as in words such as الصلـاوة ,  الزكـاوةand الحيـاوة ،, including what happens in what is known as (al iqlab) the substitution, which is the inversion of the Noon Sakeena and Tanween  into meem at the ba, so the decree is the Noon or tanween, and the pronounced one is the meem, in the form of أنـمبأهم,   أنْم بوركand  هنيأم بما. The  al-hamz almusahal بين بين and al-Hamz almubadal  have been drawn  by the taghdirah, as the taghdirah formally replaces the deleted hamza, but the operative hamza is the Alif, or the lengthened yaa, or the lengthened waw, in the case of the al-hamz almusahal. And it is pronounced as a soft yā’ or a soft wāw  in the case of substitution, and all of these changes in the pronounced and decreed are caused by the juxtaposition of the letters and their closeness in the nouns and adjectives.The research reached results, the most important of which are that the double drawing of letters is due to the phonetic rules that impose it, and that the independence of the two adjacent words has an impact on this, and that some connection in words is arbitrary and not real and has its effect in drawing; in addition to the relationships of proximity and juxtaposition, the relationship between the letter and its symbol is affected by the historical relationship of writing letters, and is subject to the principle of evolution.